PENGEMBANGAN BAHAN AJAR MATERI PENILAIAN OTENTIK MATA KULIAH EVALUASI PEMBELAJARAN - Purnomo, Heru (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This study aims to produce a learning resource as a result of the improvement of teaching material of Authentic Assessment Material which was expected to have feasibility and effectiveness that fits the learning evaluation needs at the Kuningan University PGSD. The type of this research was research and development, developing several stages of a university education product, using nine stages of application: (1) preliminary study, (2) planning, (3) initial product development, (4) initial trial, (5) reviewing return the main product produced, (6) test the field, (7) review the educational product from field trials, (8) test the field implementation, and (9) retake the final product to get the last product that is appropriate for its feasibility and effectiveness. The results of this study of improving learning resources by involving the validator to determine the validity of the product instruments used, obtained 72 results with 16 indicators presented, obtained value with a mean of 4.5 with criteria Good. Field testing is limited to 32 subjects with an average of very good answers of 84.69%, 9.69% in good category, 3.75% in good enough answers, and 1.88% in fewer answers. which is 0%. Results Field field subjects were 63 students with an average student who gave very good answers of 86.98%, good answers averaged 9.84%, for answers quite good 2.86%, while for answers Less by 0.32% and Less Once at 0%. The gain score results in an average Gain Index of 0.67 out of 63 subjects. Based on the calculation of Hake, the value is 0.67 Medium criteria. Based on the results of field implementation and gain score, it can be concluded that improvement in product learning resources for feasibility and effectiveness was as expected.